Pendampingan Pengelolaan Agrowisata Universitas Lancang Kuning Pekanbaru - Eni Suhesti; Dodi Sukma; Hadinoto Hadinoto (Asosiasi Dosen Akuntansi Indonesia, 2022)
Unilak agro-tourism has the same potential as other agro-tourism, which consists of fruit plants such as; Durian, avocado, longan, honey pumpkin, peanut, long bean, cucumber, red ginger, cassava and livestock catfish and tilapia. Unilak Agrotourism has not been organized as well as Agrotourism in general, the cropping pattern is still not regular, so it is necessary to provide Unilak Agrotourism. Agro-tourism training aims to increase understanding in the context of fostering agro-tourism managers as an alternative tourist attraction. These efforts include community development in realizing synergy and agriculture that can produce social, economic growth and community organization. The method used is mentoring. Assisting the community to have knowledge of how to manage agro-tourism and cropping patterns that have a tourist attraction. The results obtained are community knowledge about agro-tourism management such as: a) the community knows the importance of the benefits of agro-tourism b) the community has understood how to identify potential attractions